Constructing Interculturalism: Education Policy, Cultural Diversity and Inequality in Ecuador - Marta Rodríguez Cruz (Íconos)
Together with the discourse of difference, interculturalism has formed part of the political and pedagogical agenda in Ecuador over the past decade. With the intention of deepening the study of the uses and abuses of these discourses in bilingual-intercultural education, we present the results of an ethnographic research project on these issues. The objective of this research was to analyse to what point the recognition of difference and cultural diversity in public education policy is correlated with the actual practices of bilingual intercultural education. We also analyse the consequences these policies have on the situation of poverty and inequality faced by the indigenous population and to what extent these policies allow for the practice and construction of interculturalism.